Healthcare Federalism in an Age of Nation-to-Nation Interaction - Da Silva, Michael (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 2022)
Primary provincial responsibility over healthcare in Canada has consistently produced sub-optimal results, but any increased federal role in healthcare faces familiar hurdles. Attempts to optimize the system by shifting at least some responsibilities to the federal government are undermined by a lack of clarity on the constitutionally acceptable and morally optimal contours of a central (if not primary) federal responsibility. Resolving this apparent dilemma is crucial if we are to achieve enhanced healthcare performance and healthcare justice in Canada. Yet even an increased federal role capable of surmounting those hurdles faces another, often-overlooked problem: a case can be made that the recognition of sub-state nations (e.g., the Québécois and Indigenous nations) in Canada would require the admission of their claims to greater authority over healthcare. This study examines this potential additional obstacle by setting out the options for an increased federal role in healthcare and how they interact with legitimate sub-state nationalist claims. It ultimately demonstrates that there is no ideal option for balancing those competing values. Even the best option – a national healthcare strategy – raises a number of moral issues. Yet this need not lead to an impasse. An explanation of the relevant moral concerns and analysis of the relevant policy options instead demonstrates the need to make trade-offs between values in determining who should make healthcare policy decisions in a state. The provision of examples of how one can approach the weighing of values to arrive the least bad option in this sphere should be valuable for Canadians and scholars working in this domain in other multinational states.